Fisheries Processing Strategy In Jakarta In Improving Employee Performance - Ian Nurpatria Suryawan (Jurnal Manajemen, 2022)
The owner of a fishery processing business in Jakarta seeks to improve employee performance by providing career development, good compensation, carrying out a recruitment strategy, and conducting a selection process. The population in this study was 6 (six) fishery processing businesses in Jakarta with a sample of 119 employees who were taken at random and only employees of the fishery processing department so that the sample taken did not include employees who had positions. Data collection was carried out in February 2022. The data processing used accidental sampling method. Results by research prove that career development can increase compensation and employee performance, recruitment strategy can increase compensation, selection can increase compensation, and employee performance and compensation can increase employee performance. Compensation does not significantly mediate career development, recruitment strategy, and selection of employee performance.